Phyllodes tumor, cardiovascular and chronic renal disease in a young lady on hormone replacement therapy: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Hormonal replacement therapy (HRT) has been associated with anincreased risk of developing breast cancer. The level of risk varies with different types ofHRT and the duration of use. Phyllodes tumor accounts for less than 1% of all breastneoplasms and is associated with Li-Fraumeni syndrome.Case presentation: A 37-year-old nulliparous woman presented with a left breast lump.Histological examination revealed a spindle cell neoplasm consistent with a malignantphyllodes tumor. She was diagnosed at age of 12 with ovarian dysgerminoma, hadsubtotal hysterectomy and right oophorectomy, radiotherapy and chemotherapy. Shehas been on HRT with conjugated equine estrogens for 13 years and tibolone for thelast 5 years. Following the diagnosis of phyllodes tumor, a mastectomy was performed,and HRT was changed to vaginal estrogen gel.Conclusion: Hormonal replacement therapy may pose a risk for certain types of breastcancer, especially with prolonged use of combined therapy. Patients who developcancers early in life, as well as those on HRT, require close follow-up and adequatepatient education with an emphasis on self-breast examination. Sensitization ofhealthcare providers and patients on the value of genetic screening would facilitateearly identification of such patients and follow-up at high-risk clinics.